Exposure to Family Violence, Peer Attachment, and Adolescent-to-parent Violence. Issue 7 (April 2022) - Nam, Boyoung; Kim, Jae Yop; Bright, Charlotte Lyn; Jang, Daeyeon
Although parent violence has been extensively investigated in the literature, few studies have examined its link to adult-initiated family violence. This study investigated the relationship between adult-initiated family violence (i.e., child exposure to intimate partner violence [CEIPV] and child abuse) and adolescent-to-parent violence (APV), with a particular focus on the moderating effect of peer attachment on this relationship. A sample of 709 adolescents from the Children and Adolescent Survey (a subset of the 2010 Nationwide Survey of Domestic Violence in South Korea) was used. The survey included measures of child abuse, CEIPV, APV, peer attachment, and demographic characteristics. Multiple regression analysis was conducted to examine the association between two types of adults-initiated family violence and APV. The interaction terms of peer attachment were included in the regression analysis to test its moderating effect. The results indicate that child abuse victimization is significantly associated with APV, but peer attachment significantly buffers the negative effect of child abuse on APV. CEIPV was not significantly associated with APV. The findings of the current study highlight the importance of breaking cycles of violence and improving children's relationships with their peers in preventing parent violence. Counselors and social workers should explore APV perpetrators' child abuse history when conducting interventions. School counseling programs can help reduce adolescents' violent behaviors towards their parents by promoting positive peer relationships and peer bonding.